International Human Rights Treaties in Central American Jurisdictions: Interpretative Guidelines and Principles for the International Convention on the Protection of the Rights of All Migrant Workers and Members of Their Families - Chacón Mata, Alfonso (2017)
As part of the Institute for Latin American Studies (IDELA) project on Current Migration Trends in Latin America, an analysis of the regional regulations on human rights is conducted in this paper in order to highlight efforts for an interpretative harmonization, and to ulteriorly study the possibilities of building regional regulations. The scope of the international human rights law is reviewed, since the international treaties protecting such rights include the protection of migrants as a vulnerable social group within this perspective